The reformation atonement theory of penal substitution : a systematic-theological study of its coherence with divine justice - Veldsman, Daniel Petrus (University of Pretoria, 2024)
Dissertation (MTh (Dogmatics and Christian Ethics))--University of Pretoria, 2023.